Determinan struktur modal pada perusahaan di Bursa Efek Indonesia yang terdaftar di LQ45 - Muhani, Muhani; Ferliany, Anissha; Setyawati, Irma (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to identify and analyze the determinants of capital structure in industries on the Indonesia Stock Exchange and listed on LQ 45. This research uses a quantitative approach using panel data. The sampling method is purposive sampling. This research uses secondary data originating from industrial financial reports published for the 2017-2019 period. The results show that the asset structure proxied by the Fixed Asset Ratio has a positive and significant impact on capital as proxied by the Debt to Equity Ratio, sales developments are proxied by the Debt to Equity Ratio. Sales growth and company size as proxied by Ln Total Assets have a positive and insignificant effect on capital structure.